Lost in Populism: Analyzing the Quality of Translations of Donald Trump’s Speeches and Quotations in Helsingin Sanomat Articles - Kaukonen, Kasperi (My University, 2025)
This thesis studies the translations of quotations in Helsingin Sanomat articles made by the current president of the United States of America, Donald Turmp, during the 2024 presidential elections by using translation quality assessment (TQA), the ideas of journalistic translation and critical discourse analysis. The aim of this thesis is to answer the question of whether the translations of Trump’s quotations in Helsingin Sanomat articles retain the original meaning behind the stated claim, from a standpoint of populism. The findings show that the translations do not retain the same meaning, as they make the translated quotations sound less assertive or less populist although they are considered proper translations according to the principles of TQA. To combat the rise of populist speech being translated in news media, all journalists should undergo proper training to receive knowledge of how to properly translate populist speech to retain the original meaning.
Keywords: Donald Trump, United States of America, Populism, Translation, Helsingin Sanomat, Politics